Analyses of Gen Z’s Perceived Environmental Knowledge and Intention to Use Eco-Friendly Shopping Bags - Anggraeny, Chuurur (APPS Publications, 2022)
This study aims to find out how generation Z perceives environmental knowledge in relation to their intention to use environmentally friendly shopping bags. This study collected primary data from respondents via questionnaires. A 54-respondent online survey is sent throughout East Java, with a focus on Pasuruan city, in order to achieve the study’s goal. The results demonstrate that consumer attitudes are significantly influenced by environmental knowledge, which results in the intention to use environmentally friendly shopping bags. This study extends the literature by examining and demonstrating that perceived environmental knowledge and environmental awareness may contribute to attitude toward using environmental-friendly shopping bags.